Stress Tolerance of Yeasts Dominating Reverse Osmosis Membranes for Whey Water Treatment - Vitzilaiou, Eirini; Aunsbjerg, Stina D.; Mahyudin, N. A.; Knøchel, Susanne (Frontiers in Microbiology, 2020)
Filamentous yeast species belonging to the closely related Saprochaete clavata and Magnusiomyces spicifer were recently found to dominate biofilm communities on the retentate and permeate surface of Reverse Osmosis (RO) membranes used in a whey water treatment system after CIP (Cleaning-In-Place). Microscopy revealed that the two filamentous yeast species can cover extensive areas due to their large cell size and long hyphae formation. Representative strains from these species were here further characterized and displayed similar physiological and biochemical characteristics. Both strains tested were able to grow in twice RO-filtrated permeate water and metabolize the urea present. Little is known about the survival characteristics of these strains. Here, their tolerance towards heat (60, 70 and 80 ˚C) and Ultraviolet light (UV-C) treatment at 255 nm using UV-LED was assessed as well as their ability to form biofilm and withstand cleaning associated stress. According to the heat tolerance experiments, the D60 ˚C of S. clavata and M. spicifer is 16.37 min. and 7.24 min., respectively, while a reduction of 3.5 to > 4.5 log (CFU/mL) was ensured within 5 minutes at 70 ˚C. UV-C light at a dose level 10 mJ/cm2 had little effect, while doses of 40 mJ/cm2 and upwards ensured a ≥ 4log reduction in a static laboratory scale set-up. The biofilm forming potential of one filamentous yeast and one budding yeast, S. lactativora, both isolated from the same biofilm, was compared in assays employing flat-bottomed polystyrene microwells and peg lids, respectively. In these systems, employing both nutrient rich as well as nutrient poor media, only the filamentous yeast was able to create biofilm. However, on RO membrane coupons in static systems, both the budding yeast and a filamentous yeast were capable of forming single strain biofilms and when these coupons were exposed to different simulations of CIP treatments both the filamentous and budding yeast survived these. The dominance of these yeasts in some filter systems tested, their capacity to adhere and their tolerance towards relevant stresses as demonstrated here, suggest that these slow growing yeasts are well suited to initiate microbial biofouling on surfaces in low nutrient environments.